The Influence of Principal Leadership, Teacher Training, Organizational Culture, and Academic Supervision on the Performance of High School Teachers - Nurojiyah, Siti; Ananda, Rusydi; Hadijaya, Yusuf (Journal La Edusci, 2025)
This study investigates the influence of principal leadership, teacher training, organizational culture, and academic supervision on teacher performance in senior high schools in Labuhanbatu Selatan Regency. Using a quantitative approach with path analysis, data were collected from 152 teachers through questionnaires and analyzed to determine both direct and indirect relationships among the variables. The results indicate that principal leadership, teacher training, organizational culture, and academic supervision each have significant positive effects on teacher performance, both individually and collectively. Academic supervision also plays a mediating role, reinforcing the influence of leadership, training, and organizational culture on teacher performance. These findings highlight the importance of strong educational leadership, continuous professional development, and a positive school culture as key factors in enhancing teacher performance and educational quality. The study emphasizes that an integrated strategy combining effective leadership, collaborative culture, professional training, and consistent academic supervision can significantly improve the overall quality of education in senior high schools.